Renal ultrasonographic abnormalities are associated with low glomerular filtration rate calculated by scintigraphy in dogs. Issue 4 (3rd May 2019) - Mattei, Chiara; Pelander, Lena; Hansson, Kerstin; Uhlhorn, Margareta; Olsson, Ulf; Häggström, Jens; Ljungvall, Ingrid; Ley, Charles J.
Abstract: Ultrasound provides information on kidney morphology, but studies relating structural and functional abnormalities in chronic kidney disease (CKD) are lacking. The aim of this descriptive cross‐sectional study was to compare individual kidney (IK) B‐mode ultrasound abnormalities to IK glomerular filtration rate (GFR) estimated by scintigraphy normalized to plasma volume (PV) in dogs, to evaluate if ultrasonographic findings were associated with low IKGFR/PV. Eighty privately owned dogs with and without clinical suspicion of CKD were prospectively enrolled, and kidney ultrasound and IKGFR/PV were evaluated independently. Ultrasound images were assessed retrospectively for subjective abnormalities (shape, cortical, and medullary hyperechogenicity), and kidney size was measured. The normal IKGFR/PV cutoff was derived from dogs in the study group with no history and clinical signs of kidney disease and normal blood and urine results (n = 28) and was 16.84 mL/min/L. Kidneys were categorized into normal, mild, moderate, and severe ultrasound changes according to subjective ultrasound grades. Associations were found between low IKGFR/PV and abnormal kidney shape ( P = .0004), cortical hyperechogenicity ( P = .0008), medullary hyperechogenicity ( P < .0001), and low kidney volume ( P = .0092). Apart from the moderate and severe category comparison, IKGFR/PV value significantly decreased with increasing severity of category. The combination of ultrasonographic subjective abnormalities had a high sensitivity (93.8%) and moderate specificity (65.7%) for detecting low IKGFR/PV. Kidneys with normal IKGFR/PV had a low frequency of mild ultrasound changes. Findings indicate kidneys with increasing number and grade of subjective ultrasound abnormalities are more likely to have a lower IKGFR/PV.